Tbx4 interacts with the short stature homeobox gene Shox2 in limb development. Issue 5 (28th January 2014) - Glaser, Anne; Arora, Ripla; Hoffmann, Sandra; Li, Li; Gretz, Norbert; Papaioannou, Virginia E.; Rappold, Gudrun A.
ABSTRACT Background: The short stature homeodomain transcription factors SHOX and SHOX2 play key roles in limb formation. To gain more insight into genes regulated by Shox2 during limb development, we analyzed expression profiles of WT and Shox2−/− mouse embryonic limbs and identified the T‐Box transcription factor Tbx4 as a potential downstream target. Tbx4 is known to exert essential functions in skeletal and muscular hindlimb development. In humans, haploinsufficiency of TBX4 causes small patella syndrome, a skeletal dysplasia characterized by anomalies of the knee, pelvis, and foot. Results: Here, we demonstrate an inhibitory regulatory effect of Shox2 on Tbx4 specifically in the forelimbs. We also show that Tbx4 activates Shox2 expression in fore‐ and hindlimbs, suggesting Shox2 as a feedback modulator of Tbx4. Using EMSA studies, we find that Tbx4/TBX4 is able to bind to distinct T‐box binding sites within the mouse and human Shox2/SHOX2 promoter. Conclusions: Our data identifies Tbx4 as a novel transcriptional activator of Shox2 during murine fore‐ and hindlimb development. Tbx4 is also regulated by Shox2 specifically in the forelimb bud possibly via a feedback mechanism. These data extend our understanding of the role and regulation of Tbx4 and Shox2 in limb development and limb associated diseases. Developmental Dynamics 243:629–639, 2014. © 2013 Wiley Periodicals, Inc.